Molecular characterization of Fusarium spp. associated vascular wilt in passion fruit (Passiflora ligularis JUSS) - Salazar-Gonzalez, Claudia; Yela-Caicedo, Omar; Gomez-Espinoza, Bladimir (Revista de Ciencias Agrícolas, 2022)
In Colombia, vascular rotting of passion fruit (P. ligularis) caused by the fungus Fusarium is considered the most important pathological problem in the cultivation of this fruit. Plants affected by the pathogen wilt and die, causing considerable yield losses and increased production costs. The objective of this work was to determine the genetic variability of the Fusarium species associated with this disease. For this, 50 samples were collected from producing farms in three municipalities of the department of Nariño. A total of 35 isolates were characterized morphologically and molecularly. The morphological identification was carried out using taxonomic keys. Molecular characterization was performed by PCR with primers ITS1 – ITS4 and TEF1α. The PCR products were sent to Macrogen (Korea) for sequencing. Sequencing results indicated that Fusarium oxysporum f.sp. passiflorae is associated as a causal agent of the disease. In addition, the presence of Ilyonectria robusta was determined, which, has not been reported before in passion fruit plants. The phylogenetic analysis allowed determine that there was little variability among the isolates evaluated; no grouping was observed associated to the geographical origin of the samples. The morphological characters corroborated the species information obtained from the molecular analysis.